Analisis Ketepatan Waktu Penyampaian Laporan Pertanggungjawaban (LPJ) Bendahara Periode Januari 2024 Sampai Dengan September 2025 Wilayah Kerja KPPN Pontianak - Nurul Waheedatun Fatimah; Arma Yuliza (Program Studi Akuntansi Universitas Panca Bhakti, 2025)
This study aims to analyze the timeliness of the submission of the Treasurer's Accountability Report (LPJ) for the period January 2024 to September 2025 in the Pontianak KPPN work area. This study uses a qualitative descriptive approach. Data sources consist of two, namely primary data and secondary data. Primary data was obtained from interviews with Pontianak KPPN informants. Secondary data was obtained from the Treasurer's LPJ reporting documents every month for the period January 2024 to September 2025 and administrative sanction letters. The informants are the people in charge and responsible for the validation process of the Treasurer's LPJ. The results of the research conducted are that there are several work units that still experience delays in submitting the Treasurer's LPJ to the Pontianak KPPN. The delays that occur are caused by technical constraints such as SAKTI Application system constraints and errors in administering transactions in the work unit, as well as factors from human resources, both treasurers, operators, and other officers in the work unit who are in charge of the Treasurer's LPJ. The impact of these delays is that transactions in work units are hampered, the quality and credibility of work units is reduced, and administrative order and accountability in state financial management are hampered. Keywords: Timeliness Analysis, Delay Factors, Accountability Reports